Modeling a Transient Secondary Paleolunar Atmosphere: 3‐D Simulations and Analysis. Issue 10 (27th May 2019) - Aleinov, I.; Way, M. J.; Harman, C.; Tsigaridis, K.; Wolf, E. T.; Gronoff, G.
Abstract: The lunar history of water deposition, loss, and transport postaccretion has become an important consideration in relation to the possibility of a human outpost on the Moon. Very recent work has shown that a secondary primordial atmosphere of up to 10 mbar could have been emplaced ∼3.5×10 9  years ago due to volcanic outgassing from the maria. Using a zero‐dimensional chemistry model, we demonstrate the temperature dependence of the resulting major atmospheric components (CO or CO2 ). We use a three‐dimensional general circulation model to test the viability of such an atmosphere and derive its climatological characteristics. Based on these results, we then conjecture on its capability to transport volatiles outgassed from the maria to the permanently shadowed regions at the poles. Our preliminary results demonstrate that atmospheres as low as 1 mbar are viable and that permanent cold trapping of volatiles is only possible at the poles. Key Points: We confirm the viability of transient maria outgassed atmosphere for pressures from 1 to 10 mbar Three‐dimensional simulations demonstrate where volatile deposition may occur Atmospheric escape and outgassing chemistry play important roles